An Economic Instrument to Reduce the Crime Rate in Sweden - Stenis, Jan (Archives of Business Research, 2020)
Objectives Crime is one of the most important social problems, affecting public safety, children’s development, and adult socioeconomic status. The Naturally Optimised Revenue Demand in Communities, the NORDIC model was applied to reduce the crime rate. Methods The NORDIC model that formed the basis of my study, was adapted to crime prevention. The approach was tested in a realistic case study on the crime rates in Sweden. Results Governments obtained a tool to monitor, manage, and evaluate criminality. End-users including law enforcement authorities and politicians could also use the tool to redesign the crime policy. The launched model produced constructed shadow costs to induce economic incentives to reduce the crime rate. The model considered the public’s awareness of the crime. Conclusions This paper introduced a practical, economic instrument for improved management of the crime rates. The NORDIC model could be used to reduce the Swedish crime rates and its danger to health as well as to raise the public’s awareness of crime issues.